Investigation and analysis of cycles and spatial correlation model of Iranian monthly rainfalls - rahmatollah shojaei moghadam; Mostafa karampoor; behroz nasiri; naser tahmasebipour (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study is to analyze and analyze Iran's precipitation over the past half-century(1967-2017). For this purpose, the average monthly rainfall of Iran during the statistical period of 50 years was extracted from Esfazari databases (Which is provided using data from 283 stations of Synoptic and Climatology). Regression analysis was used to analyze the trend and to analyze the annual and monthly rainfall cycles of Iran, spectral analysis was used. Investigation and analysis of monthly precipitation trend indicates that except for central Zagros (Lorestan and Chaharmahal va Bakhtiari and Gorgan areas, where rainfall in winter season has increased trend), in other parts of the country and in other seasons, the trend of decline Precipitation is prevalent. The study of Iranian rainfall cycles has been shown  that Most of Iran's rainfall cycles are 2 to 4 years old and have a short term course. Meanwhile, there are two middle-cycle 25-year cycles in January-July and two long-term 50-year cycles in March and December, indicating a trend in the March and December rainfall. The two months of February and October lacked a clear cycle. The analysis of the auto-correlation model of rainfall showed that the high spatial auto-correlation model in winter was consistent with the western, southwestern and coastal of the Caspian Sea and covered about 14% of the country's. The low spatial auto-correlation model is found in sparse spots in the southern, central and southeastern regions of the country in winter and spring, and covered about 7.5% of the country's. The results of this study indicate that the overall trend of Iran's rainfall is decreasing trend and only in winter, in the small regions of the country, the increase trend is observed.